Analisis Perbandingan Penafsiran Abu Al-Nasr dan Al-Ghumarî Mengenai Keutamaan Nabi Muhammad SAW - Rokib Hajibi; Ahmad Kamaluddin; Abd. Muid N (Jurnal Inovasi Global, 2026)
This study aims to analyze and compare the interpretations of Abdul Jalil Isa Abu al-Nasr and Abdullah bin ash-Shiddîq al-Ghumarî regarding the virtues of the Prophet Muhammad (peace be upon him). The research focuses on the exegetical methods, reference sources, and interpretative approaches adopted by each scholar in presenting the prophetic merits. Using a qualitative comparative approach, the study finds that Abu al-Nasr emphasizes historical and narrative dimensions in his interpretation, whereas al-Ghumarî prioritizes hadith-based and textual arguments. These differing epistemological orientations lead to variations in understanding the texts concerning the Prophet’s virtues, while both remain within the framework of reverence toward the Messenger of Allah. This research contributes to enriching thematic tafsir studies, particularly those addressing fadhâil al-nabi within Islamic intellectual tradition.